(untitled) (Journal of Scientific Research, 2013)
The object of this paper is to introduce a permuting tri-derivation in a G-near-ring. We obtain the conditions for a prime G-near-ring to be a commutative G-ring. Keywords: Gamma-near-ring; Prime Gamma-near-ring; Commutative Gamma-ring; Permuting tri-derivation. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.13478 J. Sci. Res. 5 (2), 275-281 (2013)